In vivo evaluation of glyburide extended release trilayer matrix tablets by geomatrix - B. Ram Prasad; G. Ganesh Kumar; D.V.R.N. Bhikshapathi (International Journal of Pharmacy and Analytical Research, 2022)
The aim of the present investigation is to design and evaluate the controlled release Glyburide trilayer matrix tablets, to achieve zero-order drug release for sustained plasma concentration. Matrix tablets were prepared by direct compression whereas three-layer tablets were prepared by compressing polymer barrier layers on both sides of the core containing the drug. Formulations were prepared by usin g different grades of hydroxy propyl methyl cellulose and Ethyl cellulose. Based on the evaluation parameters, drug dissolution profile and release drug kinetics HF16 was found to be optimized formulation. In vivo bioavailability studies were carried out on the optimized formulation (HF16), mean time to attain peak drug concentration (T max) was 6.01±0.04 and 4.00±0.01h for the optimized and marketed product respectively, while mean maximum drug concentration (Cmax) was 7.21±0.03 ng/ml and 5.00±0.01 ng/ml respectively. AUC0-α and AUC0-t for optimized formulation was significantly higher (p<0.05) as compared to marketed product. A fair correlation between the dissolution profile and bioavailability for the optimized formulation was observed. The results indicate that the approach used could lead to a successful development of a controlled release formulation of the drug. The HF16 was shown significant plasma concentration with controlled release and maintained for 24 hrs with patient compliance by reducing the dosage frequency, when compared with marketed product in the efficient management of Diabetes mellitus.